PENDIDIKAN KARAKTER DALAM PERSPEKTIF SUNAH SEBAGAI UPAYA PENINGKATAN MUTU BINA PRIBADI ISLAM PADA PESERTA DIDIK DI MTS MUHAMMADIYAH ULAK LEBAR DESA ULAK LEBAR KEC. ULU OGAN KAB. OGAN KOMERING ULU - Jamjuri; Tamyis, Muhammad; Ekowati, Endang; Supadi, Ari (UNISAN JURNAL, 2024)
Character education is the core of Islamic education which was originally known as moral education. Moral education has existed since Islam was called upon by the Prophet to his companions. Along with the spread of Islam, character education has never been neglected because the Islam preached by the Prophet is Islam in the complete sense, namely wholeness in faith, charity shaleh, and moral charity. The purpose of character or moral education is to overcome the moral decline that occurs in occurs in the current generation. Character problems are problems that must be overcome together with elements of the nation. Because this is a big problem faced by the Indonesian nation in this age of advanced technology. The progress of the times turned out to be accompanied by the decline of the morals of the younger generation who became the hope of the nation. The methodology in this study is qualitative research in the form of field research which is strengthened by literature studies This research was held because moral problems are issues that must be of mutual concern. Morals or character can be grown and formed by education. Character education is one solution to this problem. Character education takes concepts from the Qur’an, the sunnah of the Prophet and the concept of the government to support the character education strengthening program (PPK) that has been launched by the government The conclusion in this study is that character education can be integrated into learning in schools in all subjects, especially the subject of Islamic Religious Education as a subject that plays a major role in instilling religious values in students. Character education is used as an effort to improve the quality of the implementation of Islamic Personal Development activities for students at DI MTS Muhammadiyah Ulak Lebar, Ulak Lebar Village, Ulu Ogan District, Ogan Ko Regency Ogan District Ogan Komering Ulu.